Orbitally Induced Variation of Tropical Cyclone Genesis Potential Over the Western North Pacific During the Mid‐Piacenzian Warm Period: A Modeling Perspective. Issue 6 (6th June 2019) - Yan, Qing; Wei, Ting; Zhang, Zhongshi; Jiang, Nanxuan
Abstract: The mid‐Piacenzian (3.264 to 3.025 Ma) is the most recent warmer‐than‐present interval in the geological past, with clear orbital‐scale variability in climate and environments. However, it remains unclear how the orbitally induced climate change may regulate the behavior of tropical cyclones (TCs). Here we use a fully coupled climate model to examine the response of TC genesis potential to different orbital configurations specific to the mid‐Piacenzian time slab. Under the Pliocene Research, Interpretation, and Synoptic Mapping version 3 boundary conditions that use modern orbital configurations, our results show that environmental conditions in the mid‐Piacenzian are less favorable for storm formation over the western North Pacific than the preindustrial. By performing a suite of sensitivity experiments, we find that orbital configurations significantly influence the magnitude and phase of genesis potential via the modification of the atmospheric thermal structure and associated large‐scale circulations. Regarding the overall favorability, increased and decreased orbitally induced insolation leads to less and more favorable conditions for storm formation over the western North Pacific, respectively. Under several extreme orbital parameters (e.g., when northern hemisphere summer insolation is at a minimum), there is an increasing favorability for genesis in the mid‐Piacenzian relative to the preindustrial. This is attributed to the fact that the orbitally induced increase in TC genesis exceeds the reduction from the Pliocene Research, Interpretation, and Synoptic Mapping version 3 boundary conditions. Our results highlight potential orbital‐scale variability in TC activity during the mid‐Piacenzian, implying possible changes in TC‐induced vertical mixing, which might play a potential role in regulating the orbital‐scale variation of tropical/global climate during the Pliocene. Key Points: Conditions are less favorable for TC genesis over the WNP in the MP using the PRISM3 boundary conditions with modern orbital parameters Increased insolation generally leads to less favorable conditions for genesis and vice versa Under several extreme orbital configurations, conditions support more storms in the MP than the preindustrial